Evaluasi Penerapan Sistem Akuntansi Penjualan Dan Penerimaan Kas Pada Perusahaan Dagang Salam Ghifari 212 Mart - Habib Salam Al Arafat; Sodik Sodik; Endah Puspitosarie (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2023)
In general, every company has a goal to make a profit. Trading companies, industrial companies, service companies, or other companies, carry out their activities to obtain or generate profits in order to maintain the existence of the company or maintain the survival of the Company itself. One way to make a profit is by buying and selling, because buying and selling is the main source of income in every company, sales activities from each type of company are different. This research was conducted at Salam Ghifari 212 Mart trading company and is a descriptiv research with a qualitative approach. Based on research that has been conducted on Salam Ghifari 212 Mart, the application of a cash sales accounting system is actually quite good. This can be seen from the ability of only one employee in one shift who can serve many consumers well and quickly enough. But in the application of the sales accounting system on credit, there are still some shortcomings such as the absence of any documents used by consumers to make purchases and also no documents in the form of purchase receipts given by the cashier to consumers. Because of this relatively new accounting system and also no further monitoring from the makers of the sales accounting system, employees of Salam Ghifari 212 Mart have difficulty identifying and also distinguishing between debit, credit, qr code scan and also bri edc transactions which cause the functions of sales, cash receipts and cash expenditures not to run effectively or efficiently.